3D and Some Other Things Missing from the Theory of Massive Star Evolution. Issue Volume 9:Issue S307(2014) (23rd January 2015) - David Arnett, W.
Abstract: This is a sketch of a 321D approximation which is nonlocal, and thus has nonzero fluxes of KE (to be published in more detail elsewhere). We plan to add this as an option to MESA. Inclusion of KE fluxes seems to help resolve the solar abundance problem (Asplund et al. 2009 ). Smaller cores may ease the explosion problems with core collapse supernova simulations.